Efectos subletales en el desarrollo de Plutella xylostella (Lepidoptera: Plutellidae) asociados a la resistencia a fipronil - Rodriguez-Rodriguez, Jose Francisco; Cerna-Chavez, Ernesto; Ochoa-Fuentes, Yisa Maria; Beltran-Beache, Mariana; Landeros-Flores, Jeronimo; Guevara-Acevedo, Luis Patricio (Instituto de Ecología, A.C., 2020)
Plutella xylostella (L.) is the main pest of Brassicaceae crops, in which it can generate considerable economic losses. Its control is based mainly on the application of chemical insecticides, but the excessive use of these pesticides has contributed to the development of resistance towards these active ingredients. Sublethal doses of insecticides can affect the physiology and behavior of insects. Lethal concentrations (LC20 and LC50) of fipronil were determined on a resistant line and a susceptible line of insects and later these concentrations were applied to third instar larvae to evaluate the percentage of pupation, weight of pupae, emergence of adults in two generations (progenitors and descendants) as well as the development times of each stage of P. xylostella. Following the application of an LC20 of fipronil, the development time was extended for more than 3 days and the fecundity decreased by more than 20% in the line resistant to fipronil. This can be an important factor for the management and control of this pest when there are problems of resistance to fipronil.